Egg Microneedle for Transdermal Delivery of Active Liraglutide (Adv. Healthcare Mater. 9/2023). Issue 9 (5th April 2023) - You, Jeongyun; Juhng, Seorin; Song, Jieun; Park, Jihyun; Jang, Mingyu; Kang, Geonwoo; Yang, Huisuk; Min, Hye Su; Shin, Jiwoo; Lee, Seri; Ko, Hyuk Wan; Jung, Hyungil
Abstract : Transdermal Drug Delivery In article 2202473 by Hyuk Wan Ko, Hyungil Jung, and co‐workers, an egg microneedle (EMN) is comprised of three main functional layers where each layers have distinct functions to enhance the drug delivery and stability. EMN allows the loaded drug to maintain the maximum drug stability, hence allowing a precise drug delivery with flexibility on drug selection. Overall, EMN is expected to provide economic and safe drug delivery platform for many transdermal delivery.